Rancang Bangun Pengaman Sepeda Motor Menggunakan RFID Berbasis Arduino - Muhammad Ridha Fauzi (Jurnal Surya Teknika, 2020)
The safety of a motorcycle is very important for vehicle owners. Until now, most motorbikes still rely only on the key to contact the vehicle itself. In the case of vehicle theft, it is very easy for the perpetrator of the theft to use the letter "T" key. Therefore an additional vehicle safety is required which is difficult to break apart from the ignition key. The purpose of this research is to design and implement motorcycle safety using Arduino-based Radio Frequency Identification (RFID) as additional vehicle safety. The author uses an RFID card / tag to add security to the vehicle starting system with a card / tag reading distance that can be read by an RFID reader. The ID code on the RFID Card must be inputted into the Arduino so that the RFID reader can read the ID Card that has been inputted into the Arduino. Based on the results of the tests that have been done, it is found that the reading distance of the RFID Card / Tag ranges from 1 cm to 3.5 cm. If the correct ID code is inputted, the electrical system is active and vice versa if the ID code entered is wrong, the buzzer will sound and the electrical system in the vehicle is not active / does not turn